Abruptly and irreversibly changing Arctic freshwaters urgently require standardized monitoring. Issue 7 (8th June 2020) - Heino, Jani; Culp, Joseph M.; Erkinaro, Jaakko; Goedkoop, Willem; Lento, Jennifer; Rühland, Kathleen M.; Smol, John P.
Abstract: Arctic regions support a wide variety of freshwater ecosystems. These naturally oligotrophic and cold‐water streams, rivers, ponds and lakes are currently being impacted by a diverse range of anthropogenic pressures, such as accelerated climate change, permafrost thaw, land‐use change, eutrophication, brownification and the replacement of northern biota with the range expansion of more southern species. Multiple stressors are rapidly changing Arctic freshwater systems as aquatic habitats are becoming more suitable for species originating from more southerly regions and thereby threatening biota adapted to cold waters. The livelihoods of Indigenous Peoples of the north will be altered when ecosystem services associated with changes in biodiversity are affected. Unfortunately, monitoring of biodiversity change in Arctic freshwaters is currently inadequate, making it difficult, if not impossible, to predict changes in ecosystem services. Synthesis and applications . We propose a three‐step approach to better address and facilitate monitoring of the rapid ecological changes that Arctic freshwater ecosystems are currently experiencing as a result of climate change. First, we should increase our efforts in the monitoring of freshwaters across all Arctic countries by setting up a network of monitoring sites and devoting more effort to a broad‐scale baseline survey using standardized methods. Second, we should enhance modelling efforts to include both ecological change and socio‐economic development. These models should help pinpoint species, ecosystems and geographical areas that are likely to show abrupt changes in response to any changes. Third, we should increase interaction among scientists, policymakers and different stakeholder groups. In particular, Indigenous Peoples must be involved in the leadership, planning and execution of monitoring and assessment activities of Arctic freshwaters. The proposed approach, which is critical to detecting the effects of climate change in the circumpolar region, has broader applications for global coordination of Arctic freshwater biomonitoring. Through routine monitoring, standardization of methods, enhanced modelling of integrated scientific and socio‐economic change, and increased collaboration within and among sectors, more effective monitoring and management of climate change impacts on freshwater biodiversity will be possible in the Arctic and globally. Abstract : We propose a three‐step approach to better address and facilitate monitoring of the rapid ecological changes that Arctic freshwater ecosystems are currently experiencing as a result of climate change. First, we should increase our efforts in the monitoring of freshwaters across all Arctic countries by setting up a network of monitoring sites and devoting more effort to a broad‐scale baseline survey using standardized methods. Second, we should enhance modelling efforts to include both ecological change and socio‐economic development. These models should help pinpoint species, ecosystems and geographical areas that are likely to show abrupt changes in response to any changes. Third, we should increase interaction among scientists, policymakers and different stakeholder groups. In particular, Indigenous Peoples must be involved in the leadership, planning and execution of monitoring and assessment activities of Arctic freshwaters. The proposed approach, which is critical to detecting the effects of climate change in the circumpolar region, has broader applications for global coordination of Arctic freshwater biomonitoring. Through routine monitoring, standardization of methods, enhanced modelling of integrated scientific and socio‐economic change, and increased collaboration within and among sectors, more effective monitoring and management of climate change impacts on freshwater biodiversity will be possible in the Arctic and globally. Editor's Choice